Co-operation between Universities in Web-based Learning - Management Issues - Reid, Austin (Proceedings of the International Conference on Networked Learning, 2002)
Based on the case of eight Colleges which cooperated in the delivery of common educational provision across all the Colleges by means of a Web-based learning environment, the paper identifies some of the reasons which lead institutions to engage in web-based learning, the reasons some seek collaborative arrangements and factors which dissuade institutions from participating. It discusses the factors that need to be addressed in reaching a cooperative agreement.